The muscarinic receptor antagonist propiverine exhibits α(1)-adrenoceptor antagonism in human prostate and porcine trigonum - Wuest, Melinda (Springer-Verlag, 2011)
PURPOSE: Combination therapy of male lower urinary tract symptoms with α(1)-adrenoceptor and muscarinic receptor antagonists attracts increasing interest. Propiverine is a muscarinic receptor antagonist possessing additional properties, i.e., block of L-type Ca(2+) channels. Here, we have investigated whether propiverine and its metabolites can additionally antagonize α(1)-adrenoceptors. METHODS: Human prostate and porcine trigone muscle strips were used to explore inhibition of α(1)-adrenoceptor-mediated contractile responses. Chinese hamster ovary (CHO) cells expressing cloned human α(1)-adrenoceptors were used to determine direct interactions with the receptor in radioligand binding and intracellular Ca(2+) elevation assays. RESULTS: Propiverine concentration-dependently reversed contraction of human prostate pre-contracted with 10 μM phenylephrine (−log IC(50) [M] 4.43 ± 0.08). Similar inhibition was observed in porcine trigone (−log IC(50) 5.01 ± 0.05), and in additional experiments consisted mainly of reduced maximum phenylephrine responses. At concentrations ≥1 μM, the propiverine metabolite M-14 also relaxed phenylephrine pre-contracted trigone strips, whereas metabolites M-5 and M-6 were ineffective. In radioligand binding experiments, propiverine and M-14 exhibited similar affinity for the three α(1)-adrenoceptor subtypes with −log K (i) [M] values ranging from 4.72 to 4.94, whereas the M-5 and M-6 did not affect [(3)H]-prazosin binding. In CHO cells, propiverine inhibited α(1)-adrenoceptor-mediated Ca(2+) elevations with similar potency as radioligand binding, again mainly by reducing maximum responses. CONCLUSIONS: In contrast to other muscarinic receptor antagonists, propiverine exerts additional L-type Ca(2+)-channel blocking and α(1)-adrenoceptor antagonist effects. It remains to be determined clinically, how these additional properties contribute to the clinical effects of propiverine, particularly in male voiding dysfunction.